2020
DOI: 10.3389/fphys.2020.596314
|View full text |Cite
|
Sign up to set email alerts
|

Lung Epithelial TRPA1 Mediates Lipopolysaccharide-Induced Lung Inflammation in Bronchial Epithelial Cells and Mice

Abstract: Toll-like receptor (TLR) 4 was originally thought to be the sole pattern recognition receptor for lipopolysaccharide (LPS). Transient receptor potential ankyrin 1 (TRPA1), a Ca 2+ -permeant channel, has been suggested as a non-TLR receptor membrane-bound sensor of LPS. We recently reported that TRPA1 is expressed in lung epithelial cells (LECs) and mediates lung inflammation induced by cigarette smoke. However, the role of TRPA1 in LPS-induced lung inflammation has not been conclusively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 41 publications
(89 reference statements)
0
14
0
Order By: Relevance
“…There is a positive relationship between the oxidation stress and the inflammation in tissues [55]. Ko et al (2020) reported that oxidation stress activated NF-κB signaling pathway, upregulated pro-inflammatory cytokines and caused inflammation in rat lung [56]. The NF-κB signaling could be activated by AFB1 in the cell line 3D4/21 [57], resulting a series of inflammatory reactions [58].…”
Section: Discussionmentioning
confidence: 99%
“…There is a positive relationship between the oxidation stress and the inflammation in tissues [55]. Ko et al (2020) reported that oxidation stress activated NF-κB signaling pathway, upregulated pro-inflammatory cytokines and caused inflammation in rat lung [56]. The NF-κB signaling could be activated by AFB1 in the cell line 3D4/21 [57], resulting a series of inflammatory reactions [58].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CGRP demonstrated an inhibitory effect on neutrophils and macrophage functions [ 46 ], and this relationship seems to deserve a closer look in the context of LPS-induced neuroinflammation. However, studies using knockout trpa1−/− mice showed reduction in inflammation, preliminarily negating this hypothesis [ 47 ]. On the other hand, the study by Hajna and colleagues [ 48 ], focused on the airway inflammation, presented a complex role for TRPA1 channels in the inflammatory response.…”
Section: Cellular Recognition Of Lpsmentioning
confidence: 99%
“…40 Oxidative stress activates the NF-κB signaling pathway, which further influences the production of inflammatory cytokines, including IL-18, IL-6, and TNF-⊍. 47 Ko et al 48 indicated that oxidation stress activated the NF-κB signaling pathway, upregulated proinflammatory cytokines and caused an inflammation in rat lung. Additionally, it is well known that TLR4 is a key functional protein that is recognized by LPS.…”
Section: Discussionmentioning
confidence: 99%